Developmental Programming of Nonalcoholic Fatty Liver Disease: The Effect of Early Life Nutrition on Susceptibility and Disease Severity in Later Life. (18th May 2015) - Li, Minglan; Reynolds, Clare M.; Segovia, Stephanie A.; Gray, Clint; Vickers, Mark H.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is fast becoming the most common liver disease globally and parallels rising obesity rates. The developmental origins of health and disease hypothesis have linked alterations in the early life environment to an increased risk of metabolic disorders in later life. Altered early life nutrition, in addition to increasing risk for the development of obesity, type 2 diabetes, and cardiovascular disease in offspring, is now associated with an increased risk for the development of NAFLD. This review summarizes emerging research on the developmental programming of NAFLD by both maternal obesity and undernutrition with a particular focus on the possible mechanisms underlying the development of hepatic dysfunction and potential strategies for intervention.